Study on Perception and Level of Peasants Participation in Parungpanjang Research Forest - NFN Desmiwati (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2016)
The aimed of this study is to analyze the perception and level of peasant participation in the management of Parungpanjang Forest Research (HP) Parungpanjang that has been run with the peasants. By this study, it is expected to provide informationand inputs for the formulation of the strategy and direction of HP Parungpanjang management policies in order to fulfill empowerment aspect of peasants and forest security. The method used was the descriptive analytical research, data were collected through surveys, Focussed Group Discussion, semi-structured interviews, observation, field notes and documentation. The measurement of perception was using Likert scale while participation level measured by Arnstein's participation ladder degree. The results showed that the perception of peasants toward HP Parungpanjang management is very good however the level of participation of peasantsis categorized in therapies level which means the Parungpanjang Forest Research still applying non-participatory management regarding peasants activities.